FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR BERAS DI INDONESIA TAHUN 1991-2021 - Azzalia, Della Fisca; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 4 (2024): Vol.13.No.4. APRIL 2024 [248-306]DO - 10.24843/EEP.2024.v13.i04.p01, 2023)
The primary goal of this study is to examine how rice consumption, rice production, local rice prices, and rice reserves collectively and partially affect rice imports in Indonesia. Additionally, it seeks to analyze the joint influence of these factors on rice imports in the country. The study employed secondary data, specifically quantitative data, collected over a period of 31 years, from 1991 to 2021, using the observation method. In the analysis, the methodology was both multiple linear regression and descriptive statistics. The research findings indicate that rice imports in Indonesia are influenced by a combination of factors, including rice consumption, rice production, local rice prices, and rice reserves. The variables related to rice production, rice consumption, and local rice prices have a partial impact on rice imports in Indonesia. However, it is noted that the variable concerning rice reserves does not significantly affect rice imports in Indonesia. keyword : Rice Production, Rice Consumption, Local Rice Prices, Rice Reserves, Rice Imports